THE CONNECTION OF EMOTIONS WITH THE MENTAL STATE OF HIGHLY QUALIFIED WRESTLERS - Sardorxon Kuvondikov (Journals Park Publishing, 2023)
The paper considers the aspect of predicting the potential of young athletes in martial arts. The author recommends using genetic markers in case of difficulties. At the same time, the method of dermatoglyphics is of great interest for use in sports selection in the practice of training a sports reserve.
Keywords: forecasting, potential opportunities, young athletes, martial arts, genetic markers, sports selection, training, sports reserve.